ANALISIS KEMISKINAN MAKRO DAN MIKRO KABUPATEN KUTAI KARTANEGARA - Sudirman Sudirman (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2014)
During the 2009-2013 period , the level of poverty in Kutai regency % decrease from 8:03 in 2009 to 7:52 % in 2013. Means for five years , only fell by 6.8 % . Slowdown in poverty reduction so that the Long Term Deveploment Plan/Recana Pembangunan Jangka Panjang (RPJMD) targets in 2015 the poverty rate to 4 % will be difficult to achieve. Poor quality of the poverty reduction program planning is one factor that causes the slowdown. Planning poverty reduction programs in Kutai regency is not based on the characteristics of the poor.Micro poverty data correlated with macro poverty data.Based on the analysis of micro data on poverty are some of the characteristics of poverty in Kutai Kartanegara Regency:(1) is unable or have difficulties to go to medical staff, unless the health center or government subsidized, (2)can not afford to send their children to high school level, (3) stay at home with his wall made of bamboo / wood / wall with the condition is not good / low quality,floor made of soil or wood / cement / ceramic with low quality,roof made of palm fiber / thatch or tile / zinc / asbestos in poor condition or low quality,lighting instead of electricity, (4) source of drinking water from wells or unprotected springs / river / rainwater, and (5) do not use the septictank as landfills feces. Poverty reduction programs should be prioritized according to the characteristics of the poor Key Words: macro poverty indicators, micro poverty indicators